Modern knitted shawls & wraps : 35 warm and stylish designs to knit, from lacy shawls to chunky afghans /: 35 warm and stylish designs to knit, from lacy shawls to chunky afghans. (2022) - Strutt, Laura, 1979-
No abstract available